ANALISIS PERPINDAHAN PANAS TUNGKU PADA TUNNEL KILN UNTUK PROSES PEMBAKARAN BATA MERAH DI PT XYZ - Irwan Suriaman; Uus Supriatna; M. Rizky Anugrah; Rohman; Dede Ardi Rajab; Yadi Heryadi; T.B.U. Adi Subekhi; Wawan (Jurnal Teknologika, 2023)
Ceramics are widely used by people in industries for various purposes, for example to make cups and tiles. Currently ceramics are widely used in various industrial raw materials. Ceramics are used as materials for making spark plugs, electrical insulators, and raw materials for printing tools. The ceramics industry is energy intensive in utilizing electrical energy. The amount of energy absorption affects the amount of costs that must be incurred by companies for energy consumption. To reduce costs used by ceramic companies during production, the use of energy is a way to increase the efficiency of the tunnel kiln. Therefore, based on these problems, research was carried out to analyze the data resulting from measurements of the large flow rate of heat transfer by conduction in the thickness of the wall, the amount of heat loss lost by convection on the outside of the wall, and the amount of loss in production costs incurred due to heat loss. This aims to obtain a solution that saves electrical energy used in the production of ceramics. So it was obtained that the highest conduction was in the top firing zone of the core from burning red bricks with heat dissipation reaching 829.73 Watts. Meanwhile, the heat lost at a distance of 50 cm and at a distance of 100 cm is the top firing zone which has the greatest heat loss of up to 0.1 MW compared to the other zones. The preheating zone reaches 5 kW and the cooling zone reaches 16 kW.